Monitoring the effects of forest clear-cutting and mongoose Herpestes auropunctatus invasion on wildlife diversity on Amami Island, Japan. Issue 2 (April 2014) - Sugimura, Ken; Ishida, Ken; Abe, Shintaro; Nagai, Yumiko; Watari, Yuya; Tatara, Masaya; Takashi, Mikio; Hashimoto, Takuma; Yamada, Fumio
Abstract Wildlife populations on Amami Island, Japan, have been affected by forest clear-felling and the introduction of alien species, in particular the mongoose Herpestes auropunctatus. We used monitoring data collected over 24 years to track changes in the population sizes of five species of mammals and 20 species of birds. We assigned species to the following groups: indigenous, rare, insectivorous, negatively affected by forest clear-cutting, and negatively affected by mongoose invasion. We examined trends in each group at four time points between 1985 and 2010 using two methods: species abundance estimates and the Living Planet Index. We then assessed the usefulness of these methods as tools for conservation planning. Inspecting species individually we identified four main patterns of abundance change: (a) an increase from the first to the last census period, (b) an increase in all periods except 2009–2010, (c) a decrease from 1985–1986 to 2001–2002 but an increase in 2009–2010, and (d) a decrease in all census periods. We observed certain relationships between these patterns and the species groups assigned as above. According to the Living Planet Index the group negatively affected by forest clear-cutting did not show significant recovery and the groups of rare species and species negatively affected by mongoose recovered to c. 40% of the original level after a sharp decline during 1985–2002. The Living Planet Index is a more useful tool for assessing the urgency of particular conservation needs, although limited information on species abundance reduces its representativeness for some groups.